Effect of hydrophilic groups on the bioactivity of antimicrobial polymers. Issue 39 (23rd September 2021) - Pham, Phuong; Oliver, Susan; Wong, Edgar H. H.; Boyer, Cyrille
Abstract : Antimicrobial polymers have recently been investigated as potential treatments to combat multidrug-resistant pathogens. Abstract : Antimicrobial polymers have recently been investigated as potential treatments to combat multidrug-resistant pathogens. A typical antimicrobial polymer consists of cationic groups that allow the polymers to adsorb onto negatively charged bacterial membranes and hydrophobic groups that insert into and disrupt the bilipid membrane. Recently, with the introduction of ternary polymer systems, neutral hydrophilic groups have been added to modulate hydrophobic/hydrophilic balance more easily. Although numerous studies have examined the effect of active components (cationic and hydrophobic groups) of antimicrobial polymers on their bioactivity, limited studies focus on hydrophilic groups. Therefore, in this study, we developed a series of statistical amphiphilic ternary polymers to systematically investigate the effect of hydrophilic groups on antibacterial activity and biocompatibility. The results revealed that, unlike the hydrophobic groups that directly disrupt the cell membrane, the hydrophilic groups have an indirect but important impact on bioactivity through tuning of the hydrophobic/hydrophilic balance and global hydrophobicity, leading to a change in the aqueous characteristics of the polymers. Therefore, in antimicrobial polymer design, an appropriate hydrophobic/hydrophilic balance as well as the structural features of the hydrophilic group, such as length, flexibility, and hydrophilicity of the hydrophilic chain, are key determinants that can be optimised to maximise biocompatibility without negatively impacting antibacterial effect.